Cobb Syndrome Manifesting as Repetitive Seizures in a 10-Year-Old Girl: A Case Report and Literature Review - Wan, Lin; Ge, Wen-Rong; Shi, Xiu-Yu; Wang, Jing; Hu, Lin-Yan; Zou, Li-Ping; Yang, Guang (Frontiers in Neurology, 2019)
Cutaneous vertebral medullary angiomatosis, also known as Cobb syndrome, is a rare segmental neurocutaneous syndrome. This syndrome is considered to be a non-hereditary congenital disease that is usually associated with arteriovenous malformations in the skin and spine. The clinical manifestations are complex because the lesions can involve the spine, spinal cord, skin and even the viscera. Here, we present the case of a 10-year-old girl who was admitted to hospital due to headache with two episodes of convulsions. Previous examination at another hospital found no evidence of any abnormalities on either cranial or intracranial vascular magnetic resonance imaging (MRI). However, the patient had a history of subcutaneous hemangioma. Following exhaustive tests at our hospital, she was diagnosed with Cobb syndrome. She received surgery, treatment for decreasing intracranial pressure and hormonal and nutritional support. She subsequently remained stable, with no recurrence of convulsions over a 9-year follow-up period. Here, we expand upon the clinical manifestations of Cobb syndrome and propose mechanisms for the underlying pathogenesis. We hope that our experience can help avoid missed diagnoses and misdiagnosis and provide more clinical evidence for early diagnosis.